Antecedents of Revisit Intention of Thai Cultural Tourist in Thailand - KORNSUPHKIT, Thanat; PHOTCHANACHAN, Sarana; CHAROERNPORNPANICHKUL, Kitti; SHOOSANUK, Chaveewan; SHOOSANUK, Ampon (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).11, 2024)
The objectives of this research are (1) to develop the causal relationship model for antecedents of revisit intention of Thai cultural tourist in Thailand and (2) to validate the causal relationship model of antecedents of revisit intention of Thai cultural tourist in Thailand with empirical data. This research adopts quantitative research utilizing a questionnaire as a tool to collect data from 416 Thai cultural tourists. This research employed non-probability sampling with quota sampling. Statistical analysis includes frequency, percentage, mean, standard deviation, and structural equation modeling. The findings of the study revealed that (1.1) travel motivation, novelty seeking and destination image positively influence the memorable experiences of Thai cultural tourist in Thailand; (1.2) travel motivation, novelty seeking, destination image and memorable experiences positively affect the satisfaction of Thai cultural tourist in Thailand; (1.3) memorable experiences and satisfaction have a positive impact on positive word of mouth of Thai cultural tourist in Thailand and (1.4) Memorable experiences, satisfaction and positive word of mouth positively influence the revisit intention of Thai cultural tourist in Thailand. The causal relationship model of antecedents of revisit intention of Thai cultural tourist in Thailand was consistent with empirical data.